(3dhGbM GdCfhGQ GdbOSjI aj efGbH GdYdeGA hGdUhajIs - (3CHhGdehGgH YHO GdhgGH Hf CMeO Hf Ydj GdTYQGfjs; (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ,J (B771 (3g` s ((3GdLGeY GdCRgQ s)
(3ChdgG (B:s
(3hHYO, agPg WHbGJ PcQJ ajgG LedI UGdMI ef efGbH GdUGdMjf hGdYdeGA GdYGedjf s
(3BNQgG (B:s
(3hcGf GdaQGZ ef JHjjV gPg GdWHbGJ Ydi jO eDdagG SfI SJ hSJjf hJSYeGFI hGdMeO ddg QH GdYGdejf s
(3GfXQ CjVkG GdfLe GdRGgQ def jQjO WQjb GdMb GdXGgQ HQbe (B2115s
(3GfXQ Qbe (B431 (3JGQjNs
(3fSNI KGfjIs
(3hgh GdWHbGJ dhSWi s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJGQjNs